AN ANALYSIS OF FIGURATIVE LANGUAGE FOUND IN SONG OF BRUNO MARS ENTITLED “GRENADE” - Fajrin, Maudy Yaser; Parmawati, Aseptiana (PROJECT (Professional Journal of English Education), 2021)
Individuals use language as a means of communication everywhere and at all times. In today's world, figurative language is often encountered in everyday life, such as in song lyrics. Figurative language is a way of describing something without saying it directly. This research aims to investigate the figurative languages found in the lyrics of the song "Grenade" by analyzing their context and attempting to decipher their meaning. The data tool is song lyrics found on the internet, and the research approach is descriptive qualitative analysis. The results revealed that this album employs figurative language such as metaphor, hyperbole, and repetition. Furthermore, the most figurative words used in the lyrics is hyperbole. Each figurative language's contextual sense is often clarified in relation to the lyric's situation. Keywords: Figurative Language, Song lyrics, Contextual Meaning